Forgiveness sebagai Kunci Psychological Well-Being Pasca Hubungan Tanpa Status - Muhammad Haykal Abdullah; Devi Puspitasari; Tatik Meiyuntariningsih (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract This research was driven by the significance of forgiveness in enhancing psychological well-being among university students who have experienced non-committed romantic relationships in Surabaya. The study aimed to examine the relationship between forgiveness and psychological well-being among active students aged 18–25. A quantitative method with a correlational approach was employed, using purposive and incidental sampling techniques involving 348 students. Data analysis through the product moment correlation test yielded a correlation coefficient of 0.883 with a significan value of 0.000 (p < 0.01), indicating a strong and highly significant positive relationship between forgiveness and psychological well-being. These findings support the hypothesis that higher levels of forgiveness are associated with greater psychological well-being among students following non-status romantic experiences. The resultseare consistent with previous studies that have linked forgiveness to improved psychological well-being. Keywords: forgiveness, psychological well-being, students, non-committed relationship, correlation. Abstrak Penelitian ini dilatarbelakangi oleh pentingnya forgiveness di dalam meningkatkan psychologicaliwell-being mahasiswa yang pernah menjalin hubungan tanpa status di Kota Surabaya. Tujuan penelitian adalah untuk mengetahui hubungan antara forgiveness serta juga psychological well-being pada mahasiswa aktif usia 18-25 tahun. Metode yang digunakan adalah kuantitatif dengan pendekatan korelasional serta juga teknik purposive serta incidental sampling terhadap 348 mahasiswa. Analisis data menggunakan uji korelasi product moment membuktikan nilai korelasi 0,883 dengan signifikansi 0,000 (<0,01), yang mengindikasikan hubungan positif serta juga sangat signifikan antara forgiveness serta juga psychological well-being. Hasil penelitian mendukung hipotesis bahwasanya semakin tinggi tingkat forgiveness, semakin tinggi pula tingkat kesejahteraan psikologis mahasiswa setelah menjalin hubungan tanpa status. Temuan ini sejalan dengan penelitian sebelumnya yang menghubungkan forgiveness dengan kesejahteraan psikologis. Kata kunci: forgiveness, psychological well-being, mahasiswa, hubungan tanpa status, korelasi.